1999
DOI: 10.1111/j.1600-0897.1999.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐Specific Glycoprotein Gene Expression in Recurrent Aborters: A Potential Correlation to Interleukin‐10 Expression

Abstract: The level of expression of the PSG11 gene in the uterine endometrium, during the peri-implantation period, correlates with the risk of pregnancy loss in some women experiencing recurrent spontaneous abortions. The ability of PSG11 to influence the secretion of IL-10 suggests that PSG11 may contribute to the local modulation of the inflammatory T helper-1 response seen in the endometrium of these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…We observed that treatment of murine macrophages with recombinant PSG22 increased the production of TGFB but not the proinflammatory mediator TNFA and IL6 [13][14][15]. Secretion of anti-inflammatory cytokines by decidual antigen presenting cells, which was observed in the present study, has been linked to the ability of these cells to promote fetal tolerance and angiogenesis.…”
Section: Psg22 Promotes Angiogenesis During Early Gestationsupporting
confidence: 45%
See 1 more Smart Citation
“…We observed that treatment of murine macrophages with recombinant PSG22 increased the production of TGFB but not the proinflammatory mediator TNFA and IL6 [13][14][15]. Secretion of anti-inflammatory cytokines by decidual antigen presenting cells, which was observed in the present study, has been linked to the ability of these cells to promote fetal tolerance and angiogenesis.…”
Section: Psg22 Promotes Angiogenesis During Early Gestationsupporting
confidence: 45%
“…For example, the ability of human PSG1, PSG6, and PSG11 and murine PSG17 and PSG18 [7,14] to stimulate interleukin 10 (IL10) secretion by macrophages and monocytes has been demonstrated [13,15], often showing cross-species reactivity. In addition, an important anti-inflammatory mediator induced by human and mouse PSG is TGFB [13].…”
Section: Introductionmentioning
confidence: 98%
“…However, in mouse and rat PSG there is no RGD motif in the N-terminal domain [15]. Pregnancy-specific glycoprotein has also been suggested to have an immunomodulatory function [16][17][18] and an embryotrophic activity [19], and to enhance platelet and white blood cell counts after bone marrow transplantation [20].…”
Section: Introductionmentioning
confidence: 99%
“…RSA also has been linked tentatively to a reduction in Th2-type reactivity. The pregnancy-specific glycoprotein PSG11, which increases secretion of IL-10, is reduced in the endometrium of women with RSA [31]. Piccinni et al [32]found that decidual T cells in women with recurrent abortions show decreased production of LIF, IL-4 and IL-10, as compared to those with normal gestation.…”
Section: Clinical Data Indicating Human Pregnancy-associated Th2 Funcmentioning
confidence: 99%
“…Other pregnancy-induced factors influencing the immune system have been identified recently. A pregnancy-specific glycoprotein encoded by the gene PSG11 stimulates secretion of the Th2-type cytokine IL-10 by monocytes [31], and is significantly lower in women with RSA than those with normal pregnancies. Placental protein 14 directly inhibits T cell proliferation and IL-2 secretion in vitro, and so is a candidate anti-inflammatory agent.…”
Section: Hormonal Regulation Of Immune Responsesin Humansmentioning
confidence: 99%